2019
DOI: 10.3847/1538-4357/ab2b95
|View full text |Cite
|
Sign up to set email alerts
|

EMPIRE: The IRAM 30 m Dense Gas Survey of Nearby Galaxies

Abstract: We present EMPIRE, an IRAM 30 m large program that mapped λ = 3–4 mm dense gas tracers at ∼1–2 kpc resolution across the whole star-forming disk of nine nearby massive spiral galaxies. We describe the EMPIRE observing and reduction strategies and show new whole-galaxy maps of HCN(1−0), HCO+(1−0), HNC(1−0), and CO(1−0). We explore how the HCN-to-CO and IR-to-HCN ratios, observational proxies for the dense gas fraction and dense gas star formation efficiency, depend on host galaxy and local environment. We find … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
141
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(165 citation statements)
references
References 138 publications
21
141
1
1
Order By: Relevance
“…With regard to the relationship between SFE dense and Σ stellar , previous studies using the J = 1 − 0 transition of HCN and/or HCO + all showed anti-correlations (Usero et al 2015;Gallagher et al 2018a;Jiménez-Donaire et al 2019), so it is somewhat surprising to see an increasing trend between SFE dense and Σ stellar in Fig. 11b.…”
Section: The Relationships Between Star-formation Efficiency Dense-gmentioning
confidence: 83%
See 1 more Smart Citation
“…With regard to the relationship between SFE dense and Σ stellar , previous studies using the J = 1 − 0 transition of HCN and/or HCO + all showed anti-correlations (Usero et al 2015;Gallagher et al 2018a;Jiménez-Donaire et al 2019), so it is somewhat surprising to see an increasing trend between SFE dense and Σ stellar in Fig. 11b.…”
Section: The Relationships Between Star-formation Efficiency Dense-gmentioning
confidence: 83%
“…11 our statistics only include data points with SNR > 3. However, their latest result based on a larger sample shows more promising trends (Jiménez-Donaire et al 2019), so the difference is more likely a physical effect. The inconsistency implies the possibly different effects of Σ stellar on HCN 4-3 and HCO + 4-3.…”
Section: The Relationships Between Star-formation Efficiency Dense-gmentioning
confidence: 99%
“…At the same time as SFE dense decreases with increasing Σ H2 (as explored in § 4.2.2), the dense gas fraction f d is observed to increase ∝ Σ 1/2 H2 (U15; Bigiel et al 2016;Gallagher et al 2018a). This empirical trend has been associated with a dependence of the dense gas fraction on pressure in the ambient ISM (Usero et al 2015;Meidt 2016;Gallagher et al 2018a;Jiménez-Donaire et al 2019), which is empirically linked to the H 2 -to-HI ratio. As a result of these nearly reverse dependencies, our model predicts that the SFR per unit molecular gas mass is maintained at a roughly constant level, independent of Σ H2 (Usero et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Bigiel et al 2008;Leroy et al 2008;Schruba et al 2011), as well as the molecular gas main sequence relation between Σ and Σ H 2 (Wong et al 2013;Lin et al 2019). The availabilty of dense gas (as traced by HCN) maps for small samples of galaxies reveals additional kpc-scale dependences, such a positive correlation between the dense gas fraction and Σ (Usero et al 2015;Bigiel et al 2016;Gallagher et al 2018;Jimenez-Donaire et al 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Likewise, although SFR correlates well with dense molecular gas mass on scales from molecular clouds to galaxies (e.g. Gao & Solomon 2004;Wu et al 2005;Lada et al 2010), the significant scatter in this relation, and anti-correlation of the star formation efficiency of dense gas on Σ , point to local environmental regulation of star formation (Usero et al 2015;Bigiel et al 2016;Gallagher et al 2018;Jimenez-Donaire et al 2019). As a result, there is significant galaxy-to-galaxy variation of the rSFMS and the SFE can vary by an order of magnitude or more within a given galaxy (e.g.…”
Section: Introductionmentioning
confidence: 98%